Improving the accuracy of Cu(ii)–nitroxide RIDME in the presence of orientation correlation in water-soluble Cu(ii)–nitroxide rulers1. Issue 19 (26th April 2019) - Ritsch, Irina; Hintz, Henrik; Jeschke, Gunnar; Godt, Adelheid; Yulikov, Maxim
Abstract : Detailed analysis of artefacts in the Cu(ii )–nitroxide RIDME experiments, related to orientation averaging, echo-crossing, ESEEM and background-correction is presented. Abstract : Orientation selection is a challenge in distance determination with double electron electron resonance (DEER) spectroscopy of rigid molecules. The problem is reduced when applying the Relaxation-Induced Dipolar Modulation Enhancement (RIDME) experiment. Here we present an in-depth study on nitroxide-detected RIDME in Cu(ii )–nitroxide spin pairs using two Cu(ii )–nitroxide rulers that are both water soluble and have comparable spin–spin distances. They differ in the type of the ligand (TAHA and PyMTA) for the Cu(ii ) ion which results in different contributions of exchange coupling. Both rulers feature substantial orientation correlation between the molecular frames of the Cu(ii ) complex and the nitroxide. We discuss how the spin–spin couplings can be accurately measured and how they can be correlated to the nitroxide resonance frequencies. In that, we pay particular attention to the suppression of nuclear modulation and of echo crossing artefacts, to background correction, and to orientation averaging. With a nitroxide observer sequence based on chirp pulses, we achieve wideband detection of all nitroxide orientations. Two-dimensional Fourier transformation of data obtained in this manner affords observer-EPR correlated RIDME spectra that enable visual understanding of the orientation correlation. The syntheses of the Cu(ii )–nitroxide rulers are presented. The synthetic route is considered to be of general use for the preparation of [metal ion complex]–nitroxide rulers, including water soluble ones.